ANALISIS POTENSI EKONOMI KABUPATEN MANGGARAI TIMUR - , NOVI RAHMAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This paper aimed to analyze the potential economic sectors or basis ini the expansion area of small island in Regency of Manggarai. Basis sector is a sector which the level specialization is higher than the same sectors in the district or province. The datas used in this research associated with the East Manggarai, including: GDP of East Manggarai at the current prices and constant 2000 prices (2008-2010), GDP at current prices and constant 2000 prices per district (2008-2010), and GDP of East Manggarai by the use of applications at current prices and at constant prices in year of 2000 (2008-2010). In addition to support the analysis, we used datas from the East Manggarai in Statistical Numbers (2009-2011), East Manggarai Agricultural Statistics (2009-2011), Village Potential Statistics of East Manggarai (2011), Indicators of Social Welfare in East Manggarai (2012), and Number of Low Developing Villages in 183 districts in Indonesia Year of 2011, obtained from the East Nusa Tenggara Central Bureau of Statistics. The analysis tools used in this research are Location Quotient (LQ) and the Income Elasticity of Demand. The Location Quotient results show that agriculture, mining-quarrying and the building or construction are the basis sectors in East Manggarai. But the dominant basis sector in every district is agriculture sector, while Borong District has the most widely sector basis, but non-agricultural sector basis. The results of the analysis of the income elasticity of demand in general show greater influence non-food consumption in the scope of districts. The income elasticity show greater influence of non-food consumption occurred in Borong, Sambi Rampas, Lambaleda, and Poco Ranaka, while in the income elasticity show greater influence of food consumption in Elar and Kota Komba. Overall conclusion from the results of this paper show that Poco Ranaka Districtâs development can be prioritized for the agricultural sector development, while Borong Districtâs development can be prioritized for the development outside of agricultural sector.